Species of the Genus Thrips (Thysanoptera, Thripidae) from the Afro-tropical Region - Mound, Laurence A. (Zootaxa, 2010)
An illustrated key is provided to distinguish the 34 species of genus Thrips reported from the Afrotropical Region, including La Réunion. Seven new synonyms are established as a result of checking type specimens; two new species are described, T. solari from Nigeria and T. kurahashii from South Africa; and the new combination Craspedothrips ghesquierei (Priesner) is established for a species described in Taeniothrips. A diagnosis is given for each species with an indication of the known distribution.